Analysis of Consumer Consideration Factors on Moderated Purchase Decisions in Online Shopping By Consumer Trust (Study on Students of Master of Management Study Program, Postgraduate at HKBP Nommensen University, Medan) - Tongam Sihol Nababan; Ferry Panjaitan; Raya Panjaitan; Pasaman Silaban; Pantas H. Silaban (Program Pascasarjana (S2-Ilmu Manajemen) Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2021)
Objective. This study aims to identify and analyze consumer considerations factors in online purchasing decisions with trust as a moderating variable. Research Methods.This research is an associative research. The population in this study were students of the Study Program of Master of Management, Postgraduate, Universitas HKBP Nommensen Medan who had made online purchases. The number of samples was 80 respondents who were taken using purposive sampling technique. Primary data collection used questionnaires and secondary data collection used literature study. Testing the hypothesis in this study used linear regression analysis and interaction test with a significance value of = 5% (0.05). Results.The results showed that the variables of consumer consideration factors and consumer confidence had a positive and significant effect on online purchasing decisions for students of Postgraduate Management Master Program. Consumer trust was able to strengthen the influence of consumer considerations factors on consumer purchasing decisions online. Conclusion.All aspects contained in these variables consisting of price, product, ease of transaction and transaction security have a significant positive influence on consumer purchasing decisions to shop online. The better and clearer the practice of prices, products, convenience and security of transactions provided by companies or individual online sellers, the easier it is for consumers to make purchasing decisions.